2014
DOI: 10.1093/molbev/msu322
|View full text |Cite
|
Sign up to set email alerts
|

Strong Artificial Selection in Domestic Mammals Did Not Result in an Increased Recombination Rate

Abstract: Recombination rates vary in intensity and location at the species, individual, sex and chromosome levels. Despite the fundamental biological importance of this process, the selective forces that operate to shape recombination rate and patterns are unclear. Domestication offers a unique opportunity to study the interplay between recombination and selection. In domesticates, intense selection for particular traits is imposed on small populations over many generations, resulting in organisms that differ, sometime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 99 publications
(120 reference statements)
2
38
0
Order By: Relevance
“…This latter result inclines support to the view that the prior discrepancy (indirect estimation in plants supportive [30], direct evidence in mammals not supportive [32]) is owing to methodological limitations of indirect inference of recombination rather than a plant–mammal difference. One might alternatively conjecture that domestication of peach may somehow be atypical.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This latter result inclines support to the view that the prior discrepancy (indirect estimation in plants supportive [30], direct evidence in mammals not supportive [32]) is owing to methodological limitations of indirect inference of recombination rather than a plant–mammal difference. One might alternatively conjecture that domestication of peach may somehow be atypical.…”
Section: Discussionsupporting
confidence: 61%
“…A correlation between domestication and high recombination rate could be owing to high recombination prior to domestication, as a form of preadaptation to domestication [31], but current evidence argues against this [30]. However, more recent sequence data-based estimates of recombination rates in mammals contradict the domestication–recombination hypothesis [32]. It is unclear whether this difference in results between analyses reflects a taxonomic (plant–mammal) or methodological (chiasmata counts versus direct recombination inference) difference.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we examined if there was an influence of artificial selection on the distribution of CO. The motivation was that strong selection and small population size—typical conditions under domestication—are expected theoretically to impose indirect selection on genetic variants that increase the CO rate (Barton & Otto, ), a prediction with mixed empirical support (Burt & Bell, ; Muñoz‐Fuentes et al., ; Rees & Dale, ; Ross‐Ibarra, ). While we see no reason why domestication should drive consistent evolution in the physical location of CO along chromosomes, we nevertheless graphed the average CO landscape for the pool of all animals classified as wild ( N = 12, Table ; a meaningful analogous analysis in plants was precluded by the low number of wild species, N = 2).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, both SNPs and short indels can induce the appearance of novel hotspots, at an estimated rate of 0.7-1.4 DSBs every 1,000 generations, as recent studies have shown in mice [Smagulova et al, 2016]. However, and despite the importance of the Prdm9 gene in modulating recombination, the existence of species such as dogs and finches [Axelsson et al, 2012;Muñoz-Fuentes et al, 2015;Singhal et al, 2015] lacking either the gene or a functional PRDM9 protein suggests the exis-Since meiotic recombination strongly influences genome evolution, mammalian recombination landscapes can be considered as a reflection of the selective forces that affect the DNA sequence itself (determined by population genetics and the evolutionary history of each taxon), the chromosomal/genome distribution of COs, and how the DNA is packaged into chromosomes during meiosis. Therefore, it is important to take into consideration the working level of resolution when analyzing variation of recombination within and among species, which can span the whole chromosome up to the finest scale (i.e., single base pairs).…”
Section: Genetic and Epigenetic Marks Of Dsbs And Recombination Hotspotsmentioning
confidence: 99%
“…Early studies [Dutrillaux, 1986] reported a correlation between the number of chiasmata and the haploid number of chromosome arms followed by subsequent studies in a wide range of mammalian species [Pardo-Manuel de Villena and Sapienza, 2001;Segura et al, 2013]. In this context, substantial progress has been made in elucidating the mechanisms that control both the formation and genome-wide distribution of COs. MLH1 recombination maps have been constructed for a wide variety of mammalian species, including humans and non-human primates [Sun et al, 2005;Codina-Pascual et al, 2006;Hassold et al, 2009;Garcia-Cruz et al, 2011;Gruhn et al, 2013Gruhn et al, , 2016Baier et al, 2014], rodents [Froenicke et al, 2002;Dumont and Payseur, 2011;Baier et al, 2014;Basheva et al, 2014;Capilla et al, 2014], pigs [Muñoz et al, 2012;Mary et al, 2014Mary et al, , 2016, bovids [Vozdova et al, 2013[Vozdova et al, , 2014Sebestova et al, 2016], and other eutherian groups such as afrotherian species, carnivorans, and insectivorans [Borodin et al, 2008;Segura et al, 2013;Muñoz-Fuentes et al, 2015].…”
Section: Variability At the Chromosomal Levelmentioning
confidence: 99%